Handbook for organisers of study visits for education and vocational training specialists - (:unkn) unknown (Office for Official Publications of the European Communities, 2009)
"The Handbook for organisers of study visits for education and vocational training specialists should support organisers in preparing and running a successful study visit. The handbook briefly outlines the study visits programme, its objectives and place in the lifelong learning programme, the roles and responsibilities of the European Commission, Cedefop, national agencies, organisers and participants. The main focus is providing practical advice and examples of good practice to make study visits achieve their goal of contributing to policy learning and policy cooperation in lifelong learning." (Herausgeber, BIBB-Doku)
Keywords: I 1.3 Austausch von Fachkräften; G 1.3.3.3 Mobilität; P 3.2 Lehrpersonal; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; Auslandsaufenthalt; Berufliche Mobilität; Bildungspersonal; EU-Programm; Best practice